Articulated rods – a novel class of molecular rods based on oligospiroketals (OSK) - Wessig, Pablo; Merkel, Roswitha; Müller, Peter (Beilstein Journal of Organic Chemistry, 2015)
We developed a new type of molecular rods consisting of two (or more) rigid units linked by a flexible joint. Consequently we called these constructs articulated rods (ARs). The syntheses of ARs were carried out by a flexible and modular approach providing access to a number of compounds with various functionalizations in terminal positions. First applications were presented with pyrene, cinnamoyl and anthracenyl labelled ARs.
Keywords: articulated rods; click chemistry; molecular rods; oligospiroketals; pyrene excimer

(untitled) - Tour, J. M. (Chem. Rev., 1996)

(untitled) - Schwab, P. F. H.; Levin, M. D.; Michl, J. (Chem. Rev., 1999)

(untitled) - Levin, M. D.; Kaszynski, P.; Michl, J. (Chem. Rev., 2000)

(untitled) - Tour, J. M. (Acc. Chem. Res., 2000)

(untitled) - Schwab, P. F. H.; Smith, J. R.; Michl, J. (Chem. Rev., 2005)

(untitled) - Sakai, N.; Mareda, J.; Matile, S. (Acc. Chem. Res., 2005)

Nanoelectronics and Information Technology - Waser, R. (Wiley-VCH, 2012)

(untitled) - Wessig, P.; Möllnitz, K.; Eiserbeck, C. (Chem. – Eur. J., 2007)

(untitled) - Wessig, P.; Möllnitz, K. (J. Org. Chem., 2008)

(untitled) - Wessig, P.; Möllnitz, K. (J. Org. Chem., 2012)

(untitled) - Müller, P.; Nikolaus, J.; Schiller, S.; Herrmann, A.; Möllnitz, K.; Czapla, S.; Wessig, P. (Angew. Chem., 2009)

(untitled) - Nikolaus, J.; Czapla, S.; Möllnitz, K.; Höfer, C. T.; Herrmann, A.; Wessig, P.; Müller, P. (Biochim. Biophys. Acta, Biomembr., 2011)

(untitled) - Grimm, C.; Meyer, T.; Czapla, S.; Nikolaus, J.; Scheidt, H. A.; Vogel, A.; Herrmann, A.; Wessig, P.; Huster, D.; Müller, P. (Chem. – Eur. J., 2013)

(untitled) - Techen, A.; Czapla, S.; Möllnitz, K.; Budach, D.; Wessig, P.; Kumke, M. U. (Helv. Chim. Acta, 2013)

(untitled) - Wessig, P.; Gerngroß, M.; Pape, S.; Bruhns, P.; Weber, J. (RSC Adv., 2014)

Click Chemistry for Biotechnology and Materials Science - Lahann, J. (Wiley-VCH, 2009)

(untitled) - Shuto, S.; Ono, S.; Hase, Y.; Kamiyama, N.; Takada, H.; Yamasihita, K.; Matsuda, A. (J. Org. Chem., 1996)

(untitled) - Rostovtsev, V. V.; Green, L. G.; Fokin, V. V.; Sharpless, K. B. (Angew. Chem., 2002)

(untitled) - Lipshutz, B. H.; Taft, B. R. (Angew. Chem., 2006)

(untitled) - Laurent, B. A.; Grayson, S. M. (J. Am. Chem. Soc., 2011)

(untitled) - Kobayashi, M.; Kurosu, M.; Wang, W.; Kitagawa, I. (Chem. Pharm. Bull., 1994)

(untitled) - Köhn, M.; Breinbauer, R. (Angew. Chem., 2004)

(untitled) - Bains, G. K.; Kim, S. H.; Sorin, E. J.; Narayanaswami, V. (Biochemistry, 2012)

Einführung in die Photochemie - Becker, H. G. O. (Deutscher Verlag der Wissenschaften, 1991)

(untitled) - Del Valle, E. M. M. (Process Biochem., 2004)

(untitled) - Nakashima, N.; Kawabuchi, A.; Murakami, H. (J. Inclusion Phenom. Mol. Recognit. Chem., 1998)